Fertility of F1 and F2 populations involving Solanum tuberosum haploids and several diploid species - Liberal, Mozart Teixeira (Pesquisa Agropecuaria Brasileira, 2024)
Thirty-one F1 and F2 progenies involving 2 Solanum tuberosum haploids (US-W 3 and US-W 4) and 13 Solanum diploid species were studied to determine the incidence of male, female and self-fertility. This work was carried out in the field, greenhouse and laboratory. The female fertility tests were made by the use of bulked pollen of at least 4 plants with which each plant in the family was pollinated. These tests were conducted in the field. Male fertility was measured by means of pollen shed, stainability, germinability and seed set following controlled sib-matings in the field. Using the decapitation technique the self fertility tests were carried out in an air-conditioned greenhouse. Most of the plants, 82.8%, flowered; 68,8% of the plants were female fertile and 61.7% were male fertile. A high degree of self incompatibility was found in the populations studied and 18.5% of the plants tested set fruits. Pollen shedding is an efficient method to evaluate male fertility, as is pollen germinality but the latter is more complicated. Pollen stainability tends to overestimate the actual male fertility. Different selections of S. phureja showed distinct behavior in respect to levels of fertility of their progemes. Differences in fertility were detected among the progenies involving the two S. tuberosum haploids. The F1 and F2 offspring involving US-W 3 are, with few exceptions, highly fertile; those involving US-W, 4 range m fertility from low to very high. The overall fertility shown by the populations studied suggests that this material will be profitable for conducting genetic and cytogenetic studies as well as for breeding potatoes at the diploid level.